Amendment with biocontrol strains increases Trichoderma numbers in mature kiwifruit (Actinidia chinensis) orchard soils for up to six months after application. (20th January 2018) - Stark, Christine H.; Hill, Robert A.; Cummings, Nicholas J.; Li, Jin-Hua
Abstract: A Trichoderma mixture was applied to kiwifruit plants in a pot experiment and to mature orchard vines to determine its effect on numbers of root-associated fungi and compare application methods into kiwifruit orchards in New Zealand. Trichoderma and other fungal numbers were recorded using a root plating technique. In the pot experiment, a significantly greater number of Trichoderma was isolated from treated compared to untreated plants 6 and 10 weeks after inoculation. Six months after application, greater numbers of Trichoderma were recovered in the orchards from Trichoderma treated vines and the increase was comparable for all application methods with over 50% of isolated fungi identified as Trichoderma compared to 33% in the water-only control. Different viable methods are available that can easily be integrated into everyday orchard management in order to introduce Trichoderma into mature kiwifruit stands. A six-monthly or more frequent application schedule seems advisable.